Toward a phylogenetic-based Generic Classification of Neotropical Lecythidaceae—I. Status of Bertholletia, Corythophora, Eschweilera and Lecythis - Huang, Ya-Yi; Mori, Scott A.; Kelly, Lawrence M. (Phytotaxa, 2015)
Lecythidaceae subfam. Lecythidoideae is limited to the Neotropics and is the only naturally occurring subfamily of Lecythidaceae in the New World. A subset of genera with zygomorphic flowers—Bertholletia, Corythophora, Eschweilera and Lecythis—comprises a group of about 125 species called the Bertholletia clade. A previous study based on plastid ndhF and trnL-F genes supported the monophyly of Corythophora but suggested that Eschweilera and Lecythis are not monophyletic. Using this study as a baseline, we sampled more taxa and sequenced more loci to address the taxonomic problems of the ambiguous genera and to determine relationships within the Bertholletia clade. Our results support the monophyly of the Bertholletia clade as previously circumscribed. In addition, Corythophora is monophyletic, and the two accessions of Bertholletia excelsa come out together on the tree. Results of the simultaneous analysis do not support the monophyly of Lecythis or Eschweilera. Lecythis consists of four main groups (the Lecythis pisonis, L. poiteaui, L. chartacea, and L. corrugata clades), the last of which is nested within Eschweilera, and Eschweilera consists of three clades (the Eschweilera integrifolia, E. tetrapetala, and Eschweilera parvifolia clades). We compare our results with the generic classification presented in the latest monograph of neotropical Lecythidaceae and make recommendations for a revised generic classification of the Bertholletia clade of Lecythidaceae.